Commitment of the DPRD of the Province of West Papua in the Implementation of the Legislative Function of Forming Regional Regulations - Iim Abdul Hosim; Markus, Dwi Pratiwi; Tuasikal, Hadi (JUSTITIA JURNAL HUKUM, 2025)
Indonesia, as a country based on law, emphasizes the supremacy of law as a basic principle. However, inconsistencies in law enforcement continue to pose significant challenges. The establishment of West Papua as a new province in 2022 raises complex governance issues, particularly in the role of the DPRD in formulating regional regulations. These regulations must be responsive to local needs and inclusive of regional cultural diversity. This study explores the DPRD's commitment to fulfilling its legislative function, identifies challenges faced in this process, and provides recommendations for improving the quality of legislation and governance. Using a juridical-sociological approach, this study combines normative legal analysis with a study of social realities in West Papua. Data were collected through interviews with DPRD members, community leaders, and academics, as well as a review of legislative documents and qualitative analysis. The findings of this study reveal that although the DPRD is trying to develop inclusive and effective Perda, challenges such as limited human resources, lack of public participation, and political dynamics affect the legislative process. However, there are opportunities to foster collaboration with traditional leaders and local organizations and utilize technology to improve legislative efficiency. This study underlines the importance of commitment, inclusiveness, and innovation in legislative functions. Strengthening the capacity of the DPRD, ensuring active public participation, and utilizing local wisdom are important steps towards achieving effective governance and sustainable development in Southwest Papua.